AN EXAMINATION OF THE MODERATION ROLE OF THIRD-PARTY FUNDS' GROWTH IN THE RELATIONSHIP BETWEEN CREDIT RISK, FINANCIAL PERFORMANCE, AND CAPITAL ADEQUACY - Titin Hartini; Niar Astaginy; Imam Jayanto (SEAN Institute, 2022)
This study aims to determine the effect of capital adequacy and credit risk on financial performance in moderation of the growth of third-party funds. The population in this study is the banking sector listed on the Indonesia Stock Exchange from 2016 to 2022 based on the purposive sampling technique, 16 companies were obtained. In this study using moderation regression analysis. The results of this study are that capital adequacy does not affect financial performance, credit risk has a negative effect on financial performance, the growth of third-party funds cannot moderate the effect of capital adequacy and credit risk on financial performance.